If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4x = 9 + x Solving 6 + 4x = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 4x + -1x = 9 + x + -1x Combine like terms: 4x + -1x = 3x 6 + 3x = 9 + x + -1x Combine like terms: x + -1x = 0 6 + 3x = 9 + 0 6 + 3x = 9 Add '-6' to each side of the equation. 6 + -6 + 3x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 9 + -6 3x = 9 + -6 Combine like terms: 9 + -6 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 13.28-2.9m=-17.54-7.5m | | 12+2g=24 | | 4r-22r=22 | | -16.85-5.2g=-13.7g+18.43+16.9g | | 7x-15=-41 | | 1+18v=19+19v | | 2(x)-5=31 | | 3-2x=2(1-x) | | 3a-(b-2a)=equation | | 9-14n=4-15n+13 | | -2u+7=-3u | | x^2+9x+20.25=-18 | | 4(l+1)=3(l+4) | | 2+8j=9+j | | 100=x(x+10) | | 2-4c=-8c-10+8c | | 8x-16y=6 | | 14=-10x+8x+2 | | 25(6-x)2-4(6-x)3= | | -3p+5=-8p | | 2.5x+5+4.5+1.5x-4.5=15 | | -8-d=10+d | | 6+77x=33x+30 | | -z=9-2z | | -2=-2x+2 | | 6-2b=-5b | | 5x-9=3x-7 | | .25r-.125+.5r=.5+r | | 3.65+e=-.4 | | 15-3x-3=12 | | 2b^2-200=0 | | 6x-10x=-40 |